Sedimentation Levels of Red Blood Cells (ESR) and its Effect on Viscosity of Blood Cells (PVC) and Glucose in Elderly People - Ibrahim, Ammal Esmaeel; Ibrahim, Suhad Abdul Azeez; Fadhel, Dhuha Hashem; Hussein, Amir Adnan (Al-Nahrain Journal of Science, 2018)
The erythrocyte sedimentation rate (ESR) is commonly used to assess the acute phase of the inflammatory response and to diagnose conditions associated with acute and chronic inflammation, including infections, cancers, and autoimmune diseases. Packed Cell Volume (PCV) is the height of the red cell column to the total height of the column of whole blood. This study included 100 healthy subject divided into two groups: females group (50) and males group (50). The increase in Erythrocyte Sedimentation Rate (E.S.R) was higher in women group than in men group. The result showed a negative correlation between the Packed Cell Volume (PCV) and ESR while there was a positive correlation between ESR with age and glucose.